Low-Dose Decitabine Monotherapy Reverses Mixed Chimerism in Adult Patients After Allogeneic Hematopoietic Stem Cell Transplantation With Myeloablative Conditioning Regimen: A Pilot Phase II Study - Wang, Ling; Wang, Li-ning; Zhou, Ji-fang; Gao, Wen-hui; Jiang, Chuan-he; Tang, Wei; Zhao, Wei-li; Hu, Jiong; Jiang, Jie-ling (Frontiers in Medicine, 2021)
T cell mixed chimerism (MC) after allogeneic stem cell transplantation (allo-HSCT) with myeloablative conditioning regimen for hematological malignancies may indicate potential engraftment failure or disease relapse. Immune modulation such as rapid tapering or stop of immunosuppression or donor lymphocyte infusion (DLI) can reverse the MC to full donor chimerism (FDC). Developed or aggravation of GVHD and related mortality is a major concern with immune modulation. In this prospective single arm study (NCT03663751), we tested the efficacy and safety of low-dose decitabine (LD-DAC, 5mg/m2 daily for 5 days and repeated every 6~8 weeks) without any immune modulation therapy. A total of 14 patients were enrolled. All patients received myeloablative conditioning regimens and MC was documented at day +30 to day +180 after allo-HSCT with donor chimerism level from 59% to 97% without documentation of minimal residual disease (MRD). A total of 11 patients (78.6%) responded favorably with increased donor chimerism level >=95%, of whom 9 patients achieved FDC. All of them maintained their response for a median of 11 months (3~22). Three patients failing to reach a sustainable favorable response eventually experienced relapse or graft failure. All three of them remained alive in remission at last follow-up after rescuing 2nd allo-HSCT. LD-DAC monotherapy was well tolerated with limited hematological and non-hematological toxicities. New-onset GVHD symptoms were observed only in 2 patients. Overall, the estimated 2-year overall survival (OS) and event-free survival (EFS) after allo-HSCT were 90.9±8.7% and 67.0±13.7% respectively. In conclusion, mixed chimerism after allo-HSCT with myeloablative conditioning could be reserved by LD-DAC alone in a majority of patients and those who obtained FDC could enjoy long-term EFS without major complications. Further prospective study is warranted to confirm its benefit with larger number of patients.